Characterization, treatment preferences, and outcomes of 390 Egyptian Graves' disease patients: a retrospective study - Tamer Mohamed Elsherbiny (SpringerOpen, 2023)
Abstract Background Graves' disease is the most common cause of thyrotoxicosis worldwide. Patient characteristics may vary according to ethnicity, iodine status, and age. Studies on characterization of Graves' disease in Egypt are lacking. The present study aims to report the patient characteristics, as well as treatment preferences and outcomes of Graves' disease patients from Alexandria, Egypt. Methods A retrospective review of demographic, biochemical, serological, sonographic, and treatment data of Graves' disease patients attending endocrinology outpatient clinic, Alexandria faculty of medicine, Egypt. Results Three hundred ninety patients were included. Females were 75.9%, peak age was 21-40 years representing 53.1%, and family history of thyroid disease was positive in 60% of patients. Overt hyperthyroidism was present in 93.9%, TSH receptor antibodies were positive in 97.1%, and thyro-peroxidase antibodies in 74.8%. Goiter was present in 72.8%, nodularity in 18.4%, and thyroid eye disease in 17.7%. Medical treatment was used in 90% of patients, surgery in 5.4%, and radioiodine in 4.3%. For patients on medical treatment, 17.7% achieved remission, 29% relapsed, and 2.85% developed hypothyroidism. Conclusion A typical Graves' disease patient in Egypt is a middle-aged female with a positive family history of thyroid disease. Overt hyperthyroidism was the most common presentation and goiter was a common sign at presentation. The sensitivity of TRAb's for diagnosing Graves' disease was excellent (97.1%). ATD's was the commonest treatment modality with a remission rate of 17.7% and a relapse rate of 29%.